An efficient CuO-γFe2O3 composite activates persulfate for organic pollutants removal: Performance, advantages and mechanism. (March 2020) - Xian, Guang; Niu, Lijun; Zhang, Guangming; Zhou, Ningyu; Long, Zeqing; Zhi, Ran
Abstract: CuO-γFe2 O3 was fabricated as a novel and effective persulfate (PS) catalyst to remove bio-refractory organic pollutants. Characterization results showed that CuO-γFe2 O3 possessed a relatively large surface area among transition metal oxides which provided favorable adsorption and activation sites for PS to degrade pollutants. There was an obvious synergy between CuO and γFe2 O3 in the composite, which played 84.7% role in Acid orange 7 (AO7) removal. Under the optimal conditions (CuO-γFe2 O3 dosage = 0.6 g L −1, PS dosage = 0.8 g L −1, unadjusted solution pH), almost complete AO7 was rapidly eliminated in 5 min. Moreover, the wide workable pH range (2−13), good stability (0.82 mg L −1 Cu leached, almost no Fe leached) and reusability (4 times) were the significant virtues of CuO-γFe2 O3 for wastewater treatment. Besides, the reaction mechanism mainly based on the interaction among Cu(II/III) and Fe(II/III) species for sulfate radical (SO4 − ) generation was emphatically elucidated by the analyses of radicals, PS utilization, TOC removal and metal chemical states. Finally, CuO-γFe2 O3 +PS system displayed desirable removal of multiple organic pollutants with different molecular structures. In light of the prominent advantages of CuO-γFe2 O3 +PS, this work extended activated PS process in treating refractory organic wastewater. Graphical abstract: Image 1 Highlights: CuO-γFe2 O3 was fabricated for activating PS to remove multiple organic pollutants. Rapid AO7 removal (5 min, 97.3%) was achieved under the optimal conditions. CuO-γFe2 O3 +PS system exhibited a wide workable pH range of 2–13. Large surface area and high reactivity of CuO-γFe2 O3 led to the effective removal. The synergy between CuO and γFe2 O3 played an important role in organics removal.